The Capacity-Building Support Activities of the Integrated Support Center for Nuclear Nonproliferation and Nuclear Security of the Japan Atomic Energy Agency - Yosuke Naoi; Kalman A Robertson; Naoko Noro (International Journal of Nuclear Security, 2016)
International cooperation is essential to support states in building the human resources necessary for maintaining and strengthening nuclear security. As the nation’s only comprehensive nuclear research and development institute, the Japan Atomic Energy Agency (JAEA) has long-standing experience developing and operating nuclear technology in all steps of the fuel cycle. The Integrated Support Center for Nuclear Nonproliferation and Nuclear Security (ISCN) was established within the JAEA in December 2010 as Japan’s Center of Excellence for nuclear security. The ISCN provides assistance with capacity building to states throughout Asia and some other regions. The objective of this article is to describe the contribution of the ISCN to human resources development in the field of nuclear security, using its contributions to regional physical protection training and computer security training as illustrative examples. This article also considers the lessons learned from the ISCN’s experience that may benefit other nuclear security training and support centers.
Keywords: Capacity building; Human resources development; Center of Excellence; Nuclear security training; Physical protection; ISCN; Hands-on training